A feminist foremother: critical essays on Rokeya Sakhawat Hossain - Quayum, Mohammad Abdul (Orient BlackSwan, 2017)
This volume looks at the life and works of Rokeya Sakhawat Hossain (1880–1932), arguably Bengal’s earliest and boldest feminist, revered as a crusader for the emancipation and advancement of women, in particular Bengali Muslim women. Through her spirited writings and her activism, Rokeya challenged the two pillars of patriarchy – hierarchical family structures and religious dogma. She demanded that the ‘family’ be restructured on the basis of gender equality. A devout Muslim, she asked that women be recognised as human beings in their own right within practices of Islam. Born into an orthodox Muslim family, for Rokeya, the most vital way in which women could empower themselves was through education. The Sakhawat Memorial Girls’ School in Kolkata, started by Rokeya in 1911, still stands as an enduring testament to that belief. This collection of biographical and critical essays places Rokeya within the socio-cultural and historical context of her times to better appreciate her literary and social contributions in the face of the formidable challenges she faced as a Bengali Muslim woman. The essays also aim to understand why the extraordinary vision she had, not just for women but for an ideal, more gender-just society, continues to be as radical, powerful and relevant today, almost a century after her death. This volume will be a valuable asset to students and scholars of women’s and gender studies, as also of South Asian literature and culture.